Answer:
x>6 that's means x is greater than 6
P/-3+(-8)=-8
p/-3-8=-8
Add 8 to each side
p/-3-8+8=-8+8
p/-3=0
Multiply both side by 3
p/-3(3)=0(3)
p=0
Check:
p/-3+(-8)=-8
Substitute p with 0
0/-3+(-8)=-8
0-8=-8
-8=-8. As a result, p=0. Hope it help!
The value of the expression will be equal to 55.
<h3>What is an expression?</h3>
The mathematical expression combines numerical variables and operations denoted by addition, subtraction, multiplication, and division signs.
Mathematical symbols can be used to represent numbers (constants), variables, operations, functions, brackets, punctuation, and grouping. They can also denote the logical syntax's operation order and other properties.
Given that 6 is added to the product of 7 and a number 7. The expression will be written as,
E = 7 x 7 + 6
E = 49 + 6
E = 55
Therefore, the value of the expression will be equal to 55.
To know more about an expression follow
brainly.com/question/11847301
#SPJ2
Answer:
y = x + 2
Step-by-step explanation:
It looks like its adding 2 everytime.
y = x + 2
To simplify the function, we need to know some basic identities involving exponents.
1. b^(ax)=(b^x)^a=(b^a)^x
2. b^(x/d) = (b^x)^(1/d) = ((b^(1/d)^x)
Now simplify f(x), where
f(x)=(1/3)*(81)^(3*x/4)
=(1/3)(3^4)^(3*x/4) [ 81=3^4 ]
=(1/3)(3^(4*3*x/4) [ rule 1 above ]
=(1/3) (3^(3*x)
=(1/3)(3^(3x)) [ or (1/3)(27^x), by rule 1 ]
(A) Initial value is the value of the function when x=0, i.e.
initial value
= f(0)
=(1/3)(3^(3x))
=(1/3)(3^(3*0))
=(1/3)(3^0)
=(1/3)(1)
=1/3
(B) the simplified base base is 3 (or 27 if the other form is used)
(C) The domain for an exponential function is all real values ( - ∞ , + ∞ ).
(D) The range of an exponential function with a positive coefficient and without vertical shift is ( 0, + ∞ ).